The concept of healthy aging at work - A. A. Gantman; Yu. Yu. Gorblyansky; E. P. Kontorovich; O. P. Ponamareva (Медицинский вестник Юга России, 2023)
Based on a thematic review of research by foreign and domestic authors, the analysis of current trends in the aging of the population and labor force as a global demographic problem is carried out. The stages of formation of ideas about healthy aging in the world and Russia are presented. The risks of the development of premature aging and the prospects of prolonging the longevity of workers in modern conditions are considered.